2020
DOI: 10.3389/fpubh.2020.569669
|View full text |Cite
|
Sign up to set email alerts
|

Anticipating the Novel Coronavirus Disease (COVID-19) Pandemic

Abstract: The COVID-19 outbreak was first declared an international public health, and it was later deemed a pandemic. In most countries, the COVID-19 incidence curve rises sharply over a short period of time, suggesting a transition from a disease-free (or low-burden disease) equilibrium state to a sustained infected (or high-burden disease) state. Such a transition is often known to exhibit characteristics of "critical slowing down." Critical slowing down can be, in general, successfully detected using many statistica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…In particular, O'Regan & Drake [21] discussed the limitations of Gaussian detrending for diseases that decline rapidly, finding that, even for slowly changing diseases, smaller window sizes did not capture the fluctuations and larger window sizes did not successfully remove the slowly varying trend. Even with its recognized limitations, Gaussian detrending is a popular method in the EWS literature for disease transitions [21,22,33,40].…”
Section: Computing Ewss From Disease Datamentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, O'Regan & Drake [21] discussed the limitations of Gaussian detrending for diseases that decline rapidly, finding that, even for slowly changing diseases, smaller window sizes did not capture the fluctuations and larger window sizes did not successfully remove the slowly varying trend. Even with its recognized limitations, Gaussian detrending is a popular method in the EWS literature for disease transitions [21,22,33,40].…”
Section: Computing Ewss From Disease Datamentioning
confidence: 99%
“…Many methods have been proposed to measure the performance of EWSs, such as thresholding EWSs with a constant value [27,28], thresholding with the long-run standard deviation [13] or using Kendall's τ statistic. Kendall's τ statistic is the most popular approach in the literature [21,22,31,[33][34][35]40], as it gives a quantitative measure of the increasing or decreasing trend of the EWS. However, the use of Kendall's τ score can be problematic as it describes the overall trend over the time period considered, with the challenge being selecting an appropriate time period.…”
Section: Performance Of Ewssmentioning
confidence: 99%
See 2 more Smart Citations
“…Inter household contact plays an agency role in malaria spreading. In India, it has been reported that cities are mainly playing the COVID-19 epicentre, which indicates a systematic spatial pattern (Kaur et al, 2020).…”
Section: Introductionmentioning
confidence: 99%